Forget me not - Soto, Julie, 1988- (Forever, 2023)
"Ama Torres has a lot of rules, but the most important one? Absolutely no relationships. Ironic given that her goal is to become the go-to wedding planner in Sacramento. But the one time she came close to her own happily-ever-after, it ended disastrously. So, when she scores the celebrity wedding of the year, Ama is ready to make her dreams into reality. The catch? The tall, gorgeous, and incredibly terse florist who she maybe almost fell in love with...and whose heart she most definitely broke. Elliot Bloom knows that flowers need only three things: light, water, and attention. Which makes them infinitely better than humans, especially certain bright, workaholic exes who are obsessed with donuts-and unfortunately for him, utterly irresistible. If living without Ama is hard, working with her might be damn near impossible. But as the wedding takes on a life of its own, Ama and Elliot are about to discover that some things can survive a complete catastrophe . . . and that love can be sweeter the second time around"--